Molecular characterization of microorganisms during cocoa-bean fermentation process (Theobroma cacao) - Machuca-Guevara, Juana Inés (2019)
Cocoa beans fermentation is a spontaneous process of post-harvest very important for the development of chocolate aroma and flavor, which involves a number of complex microbial activities. In this work, we identify the microorganisms present in cocoa beans before, during and after the fermentation process, applying DNA sequencing analysis and MALDI TOF / TOF mass spectrometry. With the first method, the predominant bacteria and yeast identified were Lactobacillus plantarum (29%), L. brevis (18%), Bacillus cereus (15%), Pediococcus acidilactici (12%), and Pichia kudriavzevii (100%). The most important peptide sequences of each identified strain by mass fingerprint were characterized too. By the second method, 51 species of microorganisms being 73.7% bacterial species and 26.3% yeast species were identified. Additionally peptide sequences responsible Vicilin protein characteristic aroma of the fermented cocoa beans and the albumin protein of 21KDa were detected.